PENGARUH PENGGUNAAN FERRITE BEAD DAN VARIASI JENIS BUSI TERHADAP TORSI DAN DAYA PADA SEPEDA MOTOR YAMAHA SOUL GT TAHUN 2012 - Dicky Febrianto; Ranto Ranto; Husin Bugis (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
The purpose of this research was to determine: (1) The effect of Ferrite Bead on Torque and Power on the Yamaha Soul GT 2012 motorcycle. (2) the effect of use variations of spark plug type on Torque and Power on the Yamaha Soul GT 2012 motorcycles. (3) The effect of Ferrite Bead and variations of spark plug on Torque and Power on the Yamaha Soul GT 2012 motorcycle. This research is a quantitative type using experimental methods. The data analysis technique used is descriptive analysis. The research was conducted using a DYNOJET tool. The population in this research was the Yamaha Soul GT 2012 motorcycle.From this results of the research, it can be concluded: (1) The use of Ferrite Bead can increase a Torque and Power on Yamaha Soul GT 2012 motorcycle. The results without the use of Ferrite Bead produces a torque of 9,77 N.m at 4502 rpm and power of 7,23 HP at 6107 rpm, while testing using a Ferrite Bead in the middle of the spark plug wire produces a torque of 10,22 N.m at 4660 rpm and power of 7,33 HP at 5438 rpm. There was an increase in torque of 4,61% and an increase of power in 1,38 %. (2) The use of variations of the spark plugs type can increase a torque and power on Yamaha Soul GT 2012 motorcycle. The highest increase in torque and power occurs in the use of Platinum spark plugs. Test result using a Standar spark plug (C7HSA) produce a torque of 9,77 N.m at 4502 rpm and power of 7,23 HP at 6107 rpm, while testing using a Platinum spark plug (CR7HGP) obtained torque of 10,21 N.m at 4650 rpm and power of 7,33 HP at 6209 rpm, and testing using a Iridium spark plug (NGK CR6HIX) obtained torque of 10,04 N.m at 4632 rpm and power of 7,27 HP at 6466 rpm. An increase in torque on the use of platinum spark plugs by 4,5 % and power by 1,38 %. While the increase in torque on the use of iridium spark plugs is 2,76 % and the power is 0,55 %. (3) Interaction of the use of Ferrite Bead and variations of spark plugs type can increase a Torque and Power on Yamaha Soul GT 2012 motorcycle. The test results show the highest Torque and Power namely the use of Ferrite Bead in the middle of spark plugs wire and the use of Platinum spark plugs with a Torque value of 10,38 N.m at 4664 rpm and a power of 7,4 HP at 6294 rpm. There was an increase in torque by 6,24% and an increase in power by 2,4 % from standard conditions.